2016
DOI: 10.21608/jacb.2016.40882
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Behavior and Cluster Analysis of Some Floral Traits Affecting Cross Breeding in The Production of Hybrid Rice Seed

Abstract: Genetic development of improved genotypes with good floral charactaristics is the an important approach in the production of hybrid rice seed. Ten rice parental lines where four of them have cytoplasmic male sterility while the other six use restorer. These ling were crossed to obtain 24 hybrid combinations, through a factorial mating design. The parental lines and their 24 F 1 hybrids were grown in randomized complete blocks design with three replications at Rice Research and Training Center Farm, Sakha Kafr … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 3 publications
(3 reference statements)
0
3
0
Order By: Relevance
“…The hybrids Pusa 3A/GZ6296R; Pusa 6A/Giza 182R; Pusa 6A/GZ6296R; IR58025A/GZ6296R; IR69625A/Gz6296R; IR70368A/ Gz6296R and IR68902A/Gz6296R were the earliest flower with significant negative superiority over check inbred and hybrid variety, Giza 178 and EHR1, respectively under both normal and saline soil conditions. These findings indicated that heterosis effects can be used to get earliness in rice hybrids (El-Mowafi, 2001;El-Mowafi et al, 2005;El-Mowafi et al, 2015 andAbd El-Hadi et al, 2016).…”
Section: Days To Headingmentioning
confidence: 95%
See 2 more Smart Citations
“…The hybrids Pusa 3A/GZ6296R; Pusa 6A/Giza 182R; Pusa 6A/GZ6296R; IR58025A/GZ6296R; IR69625A/Gz6296R; IR70368A/ Gz6296R and IR68902A/Gz6296R were the earliest flower with significant negative superiority over check inbred and hybrid variety, Giza 178 and EHR1, respectively under both normal and saline soil conditions. These findings indicated that heterosis effects can be used to get earliness in rice hybrids (El-Mowafi, 2001;El-Mowafi et al, 2005;El-Mowafi et al, 2015 andAbd El-Hadi et al, 2016).…”
Section: Days To Headingmentioning
confidence: 95%
“…Among hybrids, the estimates of heterosis ranged from 6.643 to 31.511% under normal soil condition for the hybrids IR69625A/PR3 and Pusa 6A/Giza 178R, respectively. On the other hand, the superiority over hybrid check variety EHR1 under saline soil condition ranged from 5.187 to 23.401% for the hybrids IR69625A/PR1 and Pusa 3A/PR3, respectively (El-Mowafi et al, 2015;Veeresha et al, 2015 andAbd El-Hadi et al, 2016).…”
Section: Filled Grains Panicle -1mentioning
confidence: 99%
See 1 more Smart Citation